Avian mitochondrial genomes retrieved from museum eggshell. (9th May 2019) - Grealy, Alicia; Bunce, Michael; Holleley, Clare E
Abstract: Avian eggshell is a bio‐ceramic material with exceptional properties for preserving DNA within its crystalline structure, presenting an opportunity to retrieve genomic information from extinct or historical populations of birds. However, intracrystalline DNA has only been recovered from the large, thick eggshell of palaeognaths; members of their more‐diverse sister group (neognaths) lay smaller, thinner eggs that may not exhibit the same propensity for DNA preservation. Here, we use three 40–60‐year‐old museum eggshell specimens of Australian neognath birds to determine the minimum mass of eggshell from which intracrystalline DNA can be retrieved, and to characterize the yield and quality of such DNA. In doing so, we describe the first protocol for successful extraction of intracrystalline DNA from neognath eggshells, with the view to unlocking the potential of vast museum egg collections for genetic research. We were able to retrieve DNA fragments over 200 bp in length from 10 mg of eggshell powder from all three specimens, and demonstrate that expanding the existing blow‐hole can allow sufficient material to be collected for DNA extraction while minimizing damage to the appearance and structural integrity of the egg. Furthermore, we were able to reconstruct near‐complete mitochondrial genomes at a coverage of 40‐83X through shotgun sequencing of these extracts on three NextSeq lanes. Given the current extinction and extirpation rates of many avian species world‐wide, genetic data from eggshell could provide a rapid and cost‐effective approach to examining temporal changes in avian diversity, which is not only becoming crucial for conservation management, but also serve to deepen our understanding of genome‐wide evolutionary processes.